2020
DOI: 10.1101/2020.07.07.191676
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 Nsp1 binds ribosomal mRNA channel to inhibit translation

Abstract: AbstractThe non-structural protein 1 (Nsp1), also referred to as the host shutoff factor, is the first viral protein that is synthesized in SARS-CoV-2 infected human cells to suppress host innate immune functions1,2. By combining cryo-electron microscopy and biochemical experiments, we show that SARS-CoV-2 Nsp1 binds to the human 40S subunit in ribosomal complexes including the 43S pre-initiation complex. The protein inserts its C-terminal domain at the ent… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
271
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(311 citation statements)
references
References 36 publications
40
271
0
Order By: Relevance
“…Quantification of mScarlet reporter intensities showed that MBP-Nsp1 decreased mScarlet expression by over 4-fold (p < 0.001) ( Figure 1B). These data demonstrate that SARS-CoV-2 Nsp1 potently inhibits protein translation in cells, recapitulating previous reports (Narayanan et al, 2008;Schubert et al, 2020;Thoms et al, 2020;Tohya et al, 2009).…”
Section: Sars-cov-2 Nsp1 Suppresses Translationsupporting
confidence: 90%
See 1 more Smart Citation
“…Quantification of mScarlet reporter intensities showed that MBP-Nsp1 decreased mScarlet expression by over 4-fold (p < 0.001) ( Figure 1B). These data demonstrate that SARS-CoV-2 Nsp1 potently inhibits protein translation in cells, recapitulating previous reports (Narayanan et al, 2008;Schubert et al, 2020;Thoms et al, 2020;Tohya et al, 2009).…”
Section: Sars-cov-2 Nsp1 Suppresses Translationsupporting
confidence: 90%
“…It has been shown that Nsp1 effectively suppresses the translation of host mRNAs by directly binding to the 40S small ribosomal subunit (Narayanan et al, 2008;Tohya et al, 2009). The recent cryo-electron microscopy (cryo-EM) structures indeed revealed the binding of the C-terminal domain (CT) of Nsp1 to the mRNA entry channel of the 40S (Schubert et al, 2020;Thoms et al, 2020), blocking translation. However, how SARS-CoV-2 overcomes the Nsp1-mediated translation suppression for its own replication remains an open question.…”
Section: Introductionmentioning
confidence: 99%
“…The first protein encoded in the viral genomic RNA, NSP1, directly targets the small subunit of the human ribosome to inhibit protein synthesis. Based on our findings and recent structural studies 31,32 , we suggest that NSP1 preferentially associates with the open conformation of the 40S subunit to prevent proper accommodation of mRNA during translation initiation (Fig. 6).…”
Section: Discussionsupporting
confidence: 74%
“…The high affinity of NSP1 for the 40S subunit likely demands buildup of NSP1 protein levels before translation is inhibited broadly, which may enable viral protein synthesis to proceed unimpeded during early stages of infection. Once NSP1 has accumulated, the increased translation efficiency of the viral mRNAs relative to human mRNAs we and others 32 have observed may enable the virus to synthesize sufficient amounts of viral proteins, even when translation is largely shutdown. However, it is possible that another viral protein, a different segment of the viral genome, or another mechanism (e.g., sequestration) allows the virus to evade translation inhibition.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation